Getting Ahead or Getting By: Historical Images of Adult Education - Gerriann Brower (Adult Education Research Conference, 2007)
This study investigates how still images depict adult education and how those images are situated in prevalent discourses. The focus of this study is adult education in the 1930s at the Highlander Folk School and the Works Progress Administration.